1974
DOI: 10.1073/pnas.71.3.979
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a High Affinity Nuclear Acceptor Site for Estrogen Receptor of Calf Uterus

Abstract: By means of affinity chromatography, specific nuclear acceptor sites for estradiol receptors are identified in a fraction that can be solubilized from purified nuclei with 2 M NaCl. Interaction between these acceptor sites and crude or partially purified estradiol receptor shows a high association constant (over 109 M). Receptor-acceptor interaction is dependent on physiological concentrations of 1710-estradiol; it is disrupted by high ionic strength.The nuclear acceptor sites appear to be protein in nature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
1

Year Published

1976
1976
1988
1988

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 41 publications
2
13
1
Order By: Relevance
“…A number of groups have presented evidence that specific NHPs together with the DNA were in some way involved in specifically binding the hormone-receptor complex to the chromatin and that naked DNA was unable to bind purified steroid receptors (24)(25)(26)(27)(28). Unfortunately, all these studies used only bulk chromatin and did not examine the role of specific DNA sequences in receptor binding.…”
Section: Resultsmentioning
confidence: 99%
“…A number of groups have presented evidence that specific NHPs together with the DNA were in some way involved in specifically binding the hormone-receptor complex to the chromatin and that naked DNA was unable to bind purified steroid receptors (24)(25)(26)(27)(28). Unfortunately, all these studies used only bulk chromatin and did not examine the role of specific DNA sequences in receptor binding.…”
Section: Resultsmentioning
confidence: 99%
“…The interpretation of certain experimental findings has also been justifiably challenged (Chamness et al, 1973). These problems were adroitly circumvented in the study of Puca et al (1974), in which the acceptor components were covalently Vol. 156 linked to Sepharose 4B, thus forming an insoluble matrix suitable for affinity chromatography.…”
mentioning
confidence: 99%
“…The present study is an extension of the elegant work of Puca et al (1974), particularly in seeking a plausible explanation of the specificity of hormonal responses in terms of differences in the interactions between receptor complexes and acceptor components. Hormonal specificity is expressed in two categories, termed here overt specificity and discrete specificity.…”
mentioning
confidence: 99%
“…The limited interaction of steroids with histones (15,16) could be attributed, at least in part, to trace amounts of steroid hormone receptors "contaminating" the histone fractions (17,18). Subsequent studies have shown that steroid hormone receptors can bind to histones and protamines in vitro (19)(20)(21)(22)(23), but these studies have often implied that the receptor-histone interactions were nonspecific.…”
mentioning
confidence: 99%
“…The limited interaction of steroids with histones (15, 16) could be attributed, at least in part, to trace amounts of steroid hormone receptors "contaminating" the histone fractions (17,18). Subsequent studies have shown that steroid hormone receptors can bind to histones and protamines in vitro (19)(20)(21)(22)(23), but these studies have often implied that the receptor-histone interactions were nonspecific.To explore the possibility ofdirect and specific receptor-histone interactions, we have used the estrogen receptor from rabbit uterus to address the following questions: (i) Does the estrogen receptor bind to histones? If so, do preferential interactions occur with certain histones?…”
mentioning
confidence: 99%